2014
DOI: 10.1002/jez.1897
|View full text |Cite
|
Sign up to set email alerts
|

Development and steroidogenic properties of the Bidder's organ of the tadpole of Rhinella arenarum (Amphibia, Anura)

Abstract: Several studies suggested that in anuran amphibians steroidogenic enzymes are critical for gonadal differentiation, proposing that the amount of sex steroids would adjust this differentiation. Among anurans, bufonids are important for the study of sex differentiation due to the presence of Bidder's organ (BO) that differentiates as a rudimentary ovary in the cephalic portion of the genital ridge. Considering that in adult males of Rhinella arenarum, the BO synthesizes estradiol, the main purpose of this work i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This structure differentiates as a rudimentary ovary in the anterior part of the genital ridge. It appears in both sexes early in larval life, prior to gonad differentiation [Sassone et al, 2015]. The Bidder's organs are maintained in adults of both sexes in species like Bufo bufo and Rhinella icterica, whereas they disappear in adult females of species like R. marina and R. arenarum.…”
Section: Gonad Differentiationmentioning
confidence: 92%
“…This structure differentiates as a rudimentary ovary in the anterior part of the genital ridge. It appears in both sexes early in larval life, prior to gonad differentiation [Sassone et al, 2015]. The Bidder's organs are maintained in adults of both sexes in species like Bufo bufo and Rhinella icterica, whereas they disappear in adult females of species like R. marina and R. arenarum.…”
Section: Gonad Differentiationmentioning
confidence: 92%
“…Thus, the early differentiation of follicles in the BO of R. arenarum contrasts with their late occurrence in the ovary, which reveals a remarkably wide variation of the developmental timing between both organs. Interestingly, Sassone et al (2015) reported that during larval development of R. arenarum , the BO was able to synthesize estradiol from endogenous precursors due to the aromatase enzymatic activity of Bidderian follicles, whereas the undifferentiated gonad did not express detectable amounts of aromatase. In spite of the extensive literature on BO development and structure, its function still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…horribilis, and R . marina) have been employed extensively as model organisms for various biological disciplines, such as biochemistry (e.g., Abel and Macht, 1912;Cei et al, 1968;Rash et al, 2011), developmental biology (e.g., Markovich and Regeer, 1999;Barisone et al, 2002;Brown et al, 2002), ecotoxicology (e.g., Lajmanovich et al, 2011), molecular biology (e.g., Estoup et al, 2004Estoup et al, , 2010Rollins et al, 2015;Edwards et al, 2018;Ceschin et al, 2020), and especially physiology (e.g., Houssay and Giusti, 1929;Houssay, 1949;Penhos et al, 1967;Sassone et al, 2015). This genus also contains a highly invasive species, R .…”
Section: Introduction General Overviewmentioning
confidence: 99%